2016
DOI: 10.5935/0103-5053.20160146
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transport of Silver(I) Cation Across a Bulk Liquid Membrane Containing Bis-β-enamino Ester as Ion Carrier

Abstract: Facilitated transport of silver(I) cation across a bulk liquid membrane by two synthesized ligands, bis-β-enamino ester (BBEE) and bis(benzoic acid) trioxaheptane (BBAT), as carriers dissolved in dichloromethane has been investigated. BBEE was used as a specific ion carrier for the transport of silver(I) ion. The influence of experimental parameters affecting the transport efficiency of silver(I) ion have been studied. In the presence of thiosulfate as a suitable metal ion acceptor in the receiving phase and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The literature review shows several applications of liquid membranes to real waste solutions treatment. According to the literature 23,28,29 concentration of Ag(I) ions in wastewater was between 4.0-8.0 Â 10 À4 M. Tarahomi et al 28 showed composition of silver plating and photographic waste solution in which silver concentration was 5 Â 10 À4 M at pH 3. Amiri et al 23 also showed that the derivatives of the calix [4]pyrroles dissolved in an oil and immobilized to the supported liquid membrane (SLM) based on a polypropylene matrix are effective and selective Ag(I) ion transporters.…”
Section: Modication Of Source Phase Compositionmentioning
confidence: 99%
“…The literature review shows several applications of liquid membranes to real waste solutions treatment. According to the literature 23,28,29 concentration of Ag(I) ions in wastewater was between 4.0-8.0 Â 10 À4 M. Tarahomi et al 28 showed composition of silver plating and photographic waste solution in which silver concentration was 5 Â 10 À4 M at pH 3. Amiri et al 23 also showed that the derivatives of the calix [4]pyrroles dissolved in an oil and immobilized to the supported liquid membrane (SLM) based on a polypropylene matrix are effective and selective Ag(I) ion transporters.…”
Section: Modication Of Source Phase Compositionmentioning
confidence: 99%
“…Solute transfer through systems containing liquid membranes can be significantly enhanced by adding different carriers (ligands or extraction reagents) in the liquid membrane. Mass transfer assisted by a carrier takes place as follows: (1) the carrier reacts with the target compound (solute) at the interface between feed phase and membrane phase forming a chemical complex; (2) solute-carrier complex diffuses through liquid membrane and reaches the interface between membrane and stripping phase, where the decomplexation occurs; (3) the solute is released into the stripping phase, whereas the carrier diffuses back through membrane 10 12 , 23 , 25 , 26 . A suitable carrier facilitates the solute extraction (from feed phase) and transport (through membrane phase) as well as determines its purification 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Solute transfer through systems containing liquid membranes can be significantly enhanced by adding different carriers (ligands or extraction reagents) in the liquid membrane. Mass transfer assisted by a carrier takes place as follows: (i) the carrier reacts with the target compound (solute) at the interface between feed phase and membrane phase forming a chemical complex; (ii) solute-carrier complex diffuses through liquid membrane and reaches the interface between membrane and stripping phase, where the decomplexation occurs; (iii) the solute is released into the stripping phase, whereas the carrier diffuses back through membrane [10][11][12]23,25,26 . A suitable carrier facilitates the solute extraction (from feed phase) and transport (through membrane phase) as well as determines its purification 24 .…”
Section: Introductionmentioning
confidence: 99%